Utilização do mapa espacial de radiação e dose acumulada como ferramenta para otimização de doses em pacientes e trabalhadores nas clínicas de medicina nuclear - Lopes, Pedro Henrique Silvestre (2015)
This study has as general aim to propose a spatial map of doses as an auxiliary tool in assessing the need for optimization of the workplace in nuclear medicine services. As specific aims, we assessed the workers individual dosimetry; we analyzed the facilities of the nuclear medicine services; and we evaluated environment exposure rates. The research is characterized as a case study, with an exploratory and explanatory nature. It was conducted in three Nuclear Medicine Services, all established in the Northwest of the Paraná State. Results indicated that the evaluated dose rates and workers dosimetry, in all the dependencies of the surveyed services, are within the limits of annual doses. However some exceeded the limits recommended in the standard CNEN-NN 3:01 (2014). It was concluded that the spatial map dose is an important tool for nuclear medicine services because it facilitates the visualization of areas with highest concentration of radiation, and also helps in the constant review of these measures and resources, aiding in the identification of any failures and shortcomings, providing resources to correct any issues and prevent their repetition. The spatial map dose is also important for the regular inspection, evaluating if the radiation protection objectives are being met.